Secure Authentication Protocol Implementation for V2X Communication: a Simulation Study-Case - Amaral, Emanuely Poncio do; Horstmann, Leonardo Passig; Fröhlich, Antônio Augusto (Anais do Workshop Latinoamericano de Dependabilidade e Segurança em Sistemas Veiculares (SSV), 2025)
Secure Vehicle-to-Everything (V2X) communication is a key for the development of Intelligent Transportation Systems (ITS). Compromising the sensitive data exchanged by vehicles, pedestrians and the infrastructure can lead to critical safety and privacy risks. Nevertheless, implementing robust security protocols that respect the real-time requirements of such critical applications is challenging due to the significant computational overhead of traditional PKI and the strict latency constraints of safety messages. This work investigates the application of a secure IIoT authentication protocol, proposed in previous work by the group, in the context of V2X communication. The secure protocol is implemented on a V2X simulation environment built over the Artery framework (which integrates OMNeT++ and SUMO) and accounts for vehicles and Roadside Units communication. We evaluated the implementation in a 100-vehicle simulation in terms of latency and jitter, with a mean end-to-end authentication latency of 24.15 ms. The results corroborate the suitability of the secure IIoT protocol implemented here for V2X communication, demonstrating its ability to provide robust security without introducing prohibitive delays.